Using Silent Short Video to Improve Students’ Speaking Skill At Class XI of SMA Negeri 57 Maluku Tengah - Huwae, Sifra; Maruanaya, Hendrik Jacob; Lewier, Christian A (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2021)
The objective of this classroom action research (CAR) is to improve students’ speaking skill using silent short video at class XI of SMA Negeri 57 Maluku Tengah in the academic year 2022/2023. This research was conducted in two cycles, each with three meetings. The Steps were preliminary study, planning, action implementation, evaluation and reflection. The researcher worked collaboratively with the English teacher and the students to conduct this research. The data collected were in the form of qualitative and quantitative. The qualitative data were gained through Questionnaire and the quantitative data were gained from Speaking Ability Test. The result of this research showed that by using silent short video in English teaching and learning, the students’ speaking skill has improved in five main areas, vocabulary, pronunciation, grammar, fluency, and comprehension. The students were interested in learning speaking and they became actively involved in learning process. Moreover, the students were confident and fluent in speaking practice.